Carcinogenic 3-nitrobenzanthrone but not 2-nitrobenzanthrone is metabolised to an unusual mercapturic acid in rats - Linhart, Igor; Mráz, Jaroslav; Hanzlíková, Iveta; Silhánková, Alexandra; Frantík, Emil; Himl, Michal (Toxicology letters, 2012)
3-Nitrobenzanthrone (3-NBA) is an extremely potent mutagen and suspect human carcinogen found in diesel exhaust. Its isomer 2-nitrobenzanthrone (2-NBA) has also been found in ambient air. These isomers differ in mutagenicity in Salmonella by 2-3 orders of magnitude. To identify their urinary metabolites and also to assess the assumed differences in their excretion, rats were dosed orally with 2mg/kg b.w. of either 2-NBA or 3-NBA. Their urine was collected for two consecutive days after dosage. Both LC-ESI-MS and GC-MS confirmed formation of the corresponding aminobenzanthrones (ABA). Excretion of these metabolites within the first day after dosing with 2- and 3-ABA amounted to 0.32±0.06 and 0.83±0.40% of the doses, respectively, while the excretion within the second day was by one order of magnitude lower. A novel mercapturic acid metabolite of 3-NBA was identified in urine by LC-ESI-MS as N-acetyl-S-(3-aminobenzanthron-2-yl)cysteine (3-ABA-MA) by comparison with the authentic standard. Its excretion amounted to 0.49±0.15 and 0.02±0.01% of dose within the first and second day after dosing, respectively. In contrast, no mercapturic acid was detected in the urine of rats dosed with 2-NBA. Observed difference in the mercapturic acid formation between 2- and 3-NBA is a new distinctive feature reflecting differences in the critical step of their metabolism, i.e., benzanthronylnitrenium ion formation that is intrinsically associated with biological activities of these two isomers. Moreover, 3-ABA-MA is a promising candidate biomarker of exposure to the carcinogenic 3-NBA.
Keywords: benz(a)anthraceny; Animals; Rats, Wistar; Carcinogens; acetylcystein; hmotnostní spektrometrie s elektrosprejovou ionizací; magnetická rezonanční spektroskopie; Male; Air Pollutants; karcinogeny; plynová chromatografie s hmotnostně spektrometrickou detekcí; krysa rodu Rattus; Gas Chromatography-Mass Spectrometry; Benz(a)Anthracenes; zvířata; mužské pohlaví; Magnetic Resonance Spectroscopy; látky znečišťující vzduch; Spectrometry, Mass, Electrospray Ionization; Rats; potkani Wistar; Acetylcysteine